A method for preparing high-speed rail brake pad

The high-speed rail brake pad matrix is ​​prepared by wet grinding and cold press forming processes, and abrasive agent is used in the plasma spraying process, which solves the problem of insufficient wear resistance of existing high-speed rail brake pad friction materials, and achieves efficient grinding effect and stable friction performance.

CN119187572BActive Publication Date: 2025-03-14ZHEJIANG WANSAI AUTO PARTS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411708024.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-14
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The friction materials of existing high-speed rail brake pads are prone to corrosion and wear in the external environment, resulting in reduced wear resistance.

Method used

A preparation method is adopted to prepare the matrix by wet grinding and cold press forming processes, and then use abrasive agent in the plasma spraying process. The abrasive agent is formed by the new chemical bond formed by the amino-propenyl addition reaction to enhance the bonding force between molecules and improve the grinding effect.

Benefits of technology

The friction coefficient and wear resistance of high-speed rail brake pads are significantly improved, the wear amount is reduced, and the stability and efficient performance of the material are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 67467D3FDF3C2
    Figure 67467D3FDF3C2
Patent Text Reader

Abstract

The present invention relates to a method for preparing a high-speed rail brake pad, and belongs to the technical field of brake pads. The present invention wet-grinds, dries, sieves, cold-presses, and sinters iron powder, silicon dioxide powder, carbon powder, nickel powder, copper powder, and a grinding aid to obtain a matrix; the matrix is ​​then polished and rust-removed, ultrasonically cleaned, and the iron-chromium-aluminum mixed powder is heated to a molten state, and plasma spraying is performed on the surface of the matrix to obtain a high-speed rail brake pad; the grinding aid of the present invention is prepared by dioctadecylamine, propylene triphenyltin, methacrylic sodium alginate, triethanolamine, and DMF; the high-speed rail brake pad prepared by the present invention has the advantages of stable friction coefficient, low wear, good wear resistance, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brake pads, and in particular to a method for preparing a high-speed rail brake pad. Background Art

[0002] During the braking process, the load that the high-speed rail brake can bear is related to the speed of the train. The speed has a certain impact on the load capacity of the brake pads. However, generally speaking, for large-scale heavy trains such as high-speed rail brake pads, the load that the friction pads can bear is as high as more than ten tons, so the design is more complicated than that of ordinary trains. In addition, affected by environmental and geographical factors, these uncertain factors may affect its load capacity. During the driving process, the total amount of load should not exceed the limit value, otherwise it will cause safety problems.

[0003] Chinese patent CN115233019B: discloses a preparation method, product and application of a copper-based brake pad material, and relates to the technical field of powder metallurgy materials. The method comprises the following steps: Step 1, preparing copper and iron into copper-iron alloy powder, and preparing copper and tin into copper-tin alloy powder; Step 2, using the copper-iron alloy powder and copper-tin alloy powder as main components, mixing with lubricating components, friction components and auxiliary components to obtain a mixture; Step 3, pressing the mixture into a green body; Step 4, gas pressure sintering the green body to obtain a sintered copper-based brake pad.

[0004] Chinese patent CN109185369A: belongs to the technical field of automobile braking system, specifically relates to a powder metallurgy brake pad and a preparation method thereof, wherein the powder metallurgy brake pad is prepared by mixing, pressing and sintering processes, wherein the powder metallurgy brake pad comprises a friction material and a steel back, wherein the friction material comprises the following raw materials in parts by weight: 10-50 parts of iron powder, 10-50 parts of copper powder, 1-6 parts of molybdenum trioxide, 6-20 parts of graphite, 0.5-3 parts of silicon oxide, 0.5-3 parts of aluminum oxide, and 1-5 parts of nickel powder.

[0005] Chinese Patent CN110715005B: Belongs to the field of high-speed rail braking systems, specifically a method for preparing a high thermal conductivity copper-based brake pad with an oriented structure. This method uses copper as the matrix, iron and its alloys as the matrix strengthening component, graphite and the like as the lubricating component, and aluminum oxide, silicon dioxide and the like as the friction component. First, a polymer solution is pre-mixed with powders such as graphite to form a liquid, and then prepared into fibers by a spinning method, the graphite and other powders are dispersed, and the spinning liquid flow orientation is used to achieve the orientation arrangement of the graphite and other powders, and then the orientation structure is fixed by shaping with a coagulation liquid containing copper salts. Subsequently, the fibers formed by powders such as graphite are arranged and mixed with matrix materials such as copper powder, and a copper-based brake pad with a high density, high interface bonding strength and high orientation structure is prepared by a re-pressing and re-firing technology.

[0006] In the brake pads prepared by the above patents and prior art, the friction material is in direct contact with the outside world, which may reduce the wear resistance of the material due to corrosion, wear and other factors in the external environment. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a method for preparing a high-speed railway brake pad, and the operating steps are as follows:

[0008] S1: Weigh 110-120 parts of iron powder, 10-15 parts of silicon dioxide powder, 15-20 parts of carbon powder, 20-25 parts of nickel powder, 2-6 parts of copper powder, and 0.007-0.01 parts of grinding aid in parts by weight, put them into a spherical ink tank, put in steel balls, add alcohol, wet grind, dry, and sieve;

[0009] S2: cold pressing and sintering the sieved powder to obtain a matrix;

[0010] S3: The substrate is polished and degreased, ultrasonically cleaned, the iron-chromium-aluminum mixed powder is heated to a molten state, and plasma sprayed on the surface of the substrate to obtain a high-speed rail brake pad.

[0011] The wet grinding time is 200-270 minutes.

[0012] The drying temperature is 80-90°C and the drying time is 20-24h.

[0013] The cold pressing pressure is 400-600Mpa, and the time is 15-30S.

[0014] The sintering process is: firstly heating to 800°C and keeping the temperature for 40-60min; then heating to 1000-1200°C and keeping the temperature for 1-3h.

[0015] The iron-chromium-aluminum mixed powder is composed of 60-70 parts of iron powder, 25-30 parts of chromium powder and 2-6 parts of aluminum powder.

[0016] The plasma spraying process parameters are: 50-60v, 400-500A, 25-30kw.

[0017] The preparation method of the grinding aid is:

[0018] A1: Slowly add 5-10 parts of dioctadecylamine (CAS No.: 112-99-2), 0.04-0.5 parts of propylene triphenyltin (CAS No.: 76-63-1), 12-15 parts of methacrylated sodium alginate, and 2-6 parts of triethanolamine to 100-200 parts of DMF at 70-90°C, and mix and stir for 30-60 minutes to ensure that all ingredients are fully dissolved and evenly distributed;

[0019] A2: After mixing and dissolving, DMF is removed by vacuum distillation to obtain a grinding aid.

[0020] The temperature of the reduced pressure distillation is 80-120° C., the vacuum degree is 50-100 Torr, and the time is 60-90 min.

[0021] The preparation method of the methacrylated sodium alginate is as follows:

[0022] H1: Dissolve 80-100 parts of sodium alginate in deionized water to form a solution with a concentration of 1-5% w / v, and adjust the pH value to 8-9 with sodium hydroxide solution;

[0023] H2: At a temperature of 0-5°C, slowly drop 70-80 parts of methacrylic anhydride and 1-4 parts of photoinitiator 2959 into the solution of S1, control the dropping speed to keep the reaction temperature stable, and after the addition is completed, continue to react at 0-5°C for 3-5 hours, then continue to stir vigorously at room temperature for 8-12 hours, place the reaction solution in a dialysis bag and dialyze it in deionized water for 7 days, during which the water is changed 2-3 times a day, centrifuge the dialyzed solution to collect the supernatant, pre-freeze the supernatant and freeze-dry it in a freeze dryer to obtain methacrylylated sodium alginate.

[0024] Reaction mechanism

[0025] An amino group of the dioctadecylamine undergoes an amino-acryl addition reaction with acryloyltriphenyltin; an amino group of the dioctadecylamine undergoes an amino-acryl addition reaction with methacryloyl sodium alginate; and a grinding aid is obtained.

[0026] Technical Effects

[0027] The present invention provides a method for preparing a high-speed railway brake pad. Compared with the prior art, the present invention has the following significant effects:

[0028] 1. In the grinding aid of the present invention, the new chemical bond formed by the amino-propylene addition reaction of octadecylamine, triphenyltin and sodium alginate enhances the binding force between molecules, so that the grinding aid can be more effectively adsorbed on the surface of metal particles to form a stable adsorption layer; this stable adsorption layer can reduce the surface tension of metal particles and reduce the agglomeration between particles, thereby improving the grinding effect.

[0029] 2. The presence of long-chain alkyl groups provides additional steric hindrance for metal particles, preventing particle aggregation and maintaining small size and uniform distribution; this steric hindrance effect helps to improve the dispersion and stability of metal particles and further improve the grinding effect.

[0030] In summary, from the perspective of intermolecular forces, the reason why the grinding aid prepared by triphenyltin and sodium alginate-modified octadecylamine through amino-propylene addition reaction can show significant advantages in improving the grinding effect of metal particles and show excellent technical effects in the preparation of high-speed rail brake pads is that this kind of grinding aid can enhance the binding force between molecules, provide steric hindrance effect, have high chemical reaction activity and meet the requirements of environmental protection and sustainability. DETAILED DESCRIPTION

[0031] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description in combination with embodiments and comparative examples:

[0032] Friction coefficient and wear test: The test was carried out on an XD-MSM constant speed friction tester in accordance with GB5763-1998. The test temperature was 350°C. The test results are shown in Table 1.

[0033] Example 1

[0034] A method for preparing a high-speed rail brake pad, the operating steps of which are:

[0035] S1: Weigh 110g iron powder, 10g silicon dioxide powder, 15g carbon powder, 20g nickel powder, 2g copper powder, and 0.007g grinding aid, put them into a spherical ink tank, put in a steel ball, add alcohol, wet grind, dry, and sieve;

[0036] S2: cold pressing and sintering the sieved powder to obtain a matrix;

[0037] S3: The substrate is polished and degreased, ultrasonically cleaned, the iron-chromium-aluminum mixed powder is heated to a molten state, and plasma sprayed on the surface of the substrate to obtain a high-speed rail brake pad.

[0038] The wet grinding time is 200 min.

[0039] The drying temperature is 80° C. and the drying time is 20 hours.

[0040] The cold pressing pressure is 400Mpa and the time is 15S.

[0041] The sintering process is: firstly heating to 800°C and keeping the temperature for 40 minutes; then heating to 1000°C and keeping the temperature for 1 hour.

[0042] The iron-chromium-aluminum mixed powder is composed of: 60g iron powder, 25g chromium powder and 2g aluminum powder.

[0043] The plasma spraying process parameters are: 50v, 400A, 25kw.

[0044] The preparation method of the grinding aid is:

[0045] A1: Slowly add 5g of dioctadecylamine (CAS No.: 112-99-2), 0.04g of propylene triphenyltin (CAS No.: 76-63-1), 12-15g of sodium methacryloyl alginate, and 2g of triethanolamine into 100g of DMF at 70°C, and mix and stir for 30 minutes to ensure that all ingredients are fully dissolved and evenly distributed;

[0046] A2: After mixing and dissolving, DMF is removed by vacuum distillation to obtain a grinding aid.

[0047] The temperature of the reduced pressure distillation is 80° C., the vacuum degree is 50 Torr, and the time is 60 min.

[0048] The preparation method of the methacrylated sodium alginate is as follows:

[0049] H1: Dissolve 80 g of sodium alginate in deionized water to form a solution with a concentration of 1% w / v, and adjust the pH value to 8 with sodium hydroxide solution;

[0050] H2: At 0°C, slowly drop 70g of methacrylic anhydride and 1g of photoinitiator 2959 into the solution of S1, control the dropping speed to keep the reaction temperature stable, and after the addition is completed, continue to react at 0°C for 3 hours, then continue to stir vigorously at room temperature for 8 hours, place the reaction solution in a dialysis bag and dialyze it in deionized water for 7 days, during which the water is changed twice a day, centrifuge the dialyzed solution to collect the supernatant, pre-freeze the supernatant and freeze-dry it in a freeze dryer to obtain methacrylylated sodium alginate.

[0051] Example 2

[0052] A method for preparing a high-speed rail brake pad, the operating steps of which are:

[0053] S1: Weigh 113g iron powder, 12g silicon dioxide powder, 16g carbon powder, 22g nickel powder, 3g copper powder, and 0.008g grinding aid, put them into a spherical ink tank, put in steel balls, add alcohol, wet grind, dry, and sieve;

[0054] S2: cold pressing and sintering the sieved powder to obtain a matrix;

[0055] S3: The substrate is polished and degreased, ultrasonically cleaned, the iron-chromium-aluminum mixed powder is heated to a molten state, and plasma sprayed on the surface of the substrate to obtain a high-speed rail brake pad.

[0056] The wet grinding time is 220 min.

[0057] The drying temperature is 85°C and the drying time is 21 hours.

[0058] The cold pressing pressure is 450 MPa and the time is 20 seconds.

[0059] The sintering process is: firstly heating to 800°C and keeping the temperature for 45 minutes; then heating to 1050°C and keeping the temperature for 2 hours.

[0060] The iron-chromium-aluminum mixed powder is composed of: 63g iron powder, 26g chromium powder, and 3g aluminum powder.

[0061] The plasma spraying process parameters are: 55v, 450A, 25kw.

[0062] The preparation method of the grinding aid is:

[0063] A1: Slowly add 6g of dioctadecylamine (CAS No.: 112-99-2), 0.2g of propylene triphenyltin (CAS No.: 76-63-1), 13g of sodium methacryloyl alginate, and 3g of triethanolamine into 140g of DMF at 75°C, and mix and stir for 40 minutes to ensure that all ingredients are fully dissolved and evenly distributed;

[0064] A2: After mixing and dissolving, DMF is removed by vacuum distillation to obtain a grinding aid.

[0065] The temperature of the reduced pressure distillation is 90° C., the vacuum degree is 60 Torr, and the time is 70 min.

[0066] The preparation method of the methacrylated sodium alginate is as follows:

[0067] H1: Dissolve 85 g of sodium alginate in deionized water to form a solution with a concentration of 2% w / v, and adjust the pH value to 8 with sodium hydroxide solution;

[0068] H2: At 2°C, slowly drop 73g of methacrylic anhydride and 2g of photoinitiator 2959 into the solution of S1, control the dropping speed to keep the reaction temperature stable, and after the addition is completed, continue to react at 2°C for 3.5 hours, then continue to stir vigorously at room temperature for 9 hours, place the reaction solution in a dialysis bag and dialyze it in deionized water for 7 days, during which the water is changed twice a day, centrifuge the dialyzed solution to collect the supernatant, pre-freeze the supernatant and freeze-dry it in a freeze dryer to obtain methacrylated sodium alginate.

[0069] Example 3

[0070] A method for preparing a high-speed rail brake pad, the operating steps of which are:

[0071] S1: Weigh 118g iron powder, 14g silicon dioxide powder, 18g carbon powder, 24g nickel powder, 5g copper powder, and 0.009g grinding aid, put them into a spherical ink tank, put in a steel ball, add alcohol, wet grind, dry, and sieve;

[0072] S2: cold pressing and sintering the sieved powder to obtain a matrix;

[0073] S3: The substrate is polished and degreased, ultrasonically cleaned, the iron-chromium-aluminum mixed powder is heated to a molten state, and plasma sprayed on the surface of the substrate to obtain a high-speed rail brake pad.

[0074] The wet grinding time is 260 min.

[0075] The drying temperature is 85° C. and the drying time is 23 hours.

[0076] The cold pressing pressure is 550 MPa and the time is 25 seconds.

[0077] The sintering process is: firstly heating to 800°C and keeping the temperature for 55 minutes; then heating to 1150°C and keeping the temperature for 2.5 hours.

[0078] The iron-chromium-aluminum mixed powder is composed of: 68g iron powder, 28g chromium powder, and 5g aluminum powder.

[0079] The plasma spraying process parameters are: 55v, 450A, 30kw.

[0080] The preparation method of the grinding aid is:

[0081] A1: Slowly add 8g of dioctadecylamine (CAS No.: 112-99-2), 0.4g of propylene triphenyltin (CAS No.: 76-63-1), 14g of sodium methacryloyl alginate, and 5g of triethanolamine into 180g of DMF at 85°C, and mix and stir for 50 minutes to ensure that all ingredients are fully dissolved and evenly distributed;

[0082] A2: After mixing and dissolving, DMF is removed by vacuum distillation to obtain a grinding aid.

[0083] The temperature of the reduced pressure distillation is 110° C., the vacuum degree is 90 Torr, and the time is 80 min.

[0084] The preparation method of the methacrylated sodium alginate is as follows:

[0085] H1: Dissolve 95 g of sodium alginate in deionized water to form a solution with a concentration of 4% w / v, and adjust the pH value to 9 with sodium hydroxide solution;

[0086] H2: At 4°C, slowly drop 78g of methacrylic anhydride and 3g of photoinitiator 2959 into the solution of S1, control the dropping speed to keep the reaction temperature stable, and after the addition is completed, continue to react at 4°C for 4.5 hours, then continue to stir vigorously at room temperature for 11 hours, place the reaction solution in a dialysis bag and dialyze it in deionized water for 7 days, during which the water is changed 3 times a day, centrifuge the dialyzed solution to collect the supernatant, pre-freeze the supernatant and freeze-dry it in a freeze dryer to obtain methacrylylated sodium alginate.

[0087] Example 4

[0088] A method for preparing a high-speed rail brake pad, the operating steps of which are:

[0089] S1: Weigh 120g iron powder, 15g silicon dioxide powder, 20g carbon powder, 25g nickel powder, 6g copper powder, and 0.01g grinding aid, put them into a spherical ink tank, put in a steel ball, add alcohol, wet grind, dry, and sieve;

[0090] S2: cold pressing and sintering the sieved powder to obtain a matrix;

[0091] S3: The substrate is polished and degreased, ultrasonically cleaned, the iron-chromium-aluminum mixed powder is heated to a molten state, and plasma sprayed on the surface of the substrate to obtain a high-speed rail brake pad.

[0092] The wet grinding time is 270 min.

[0093] The drying temperature is 90° C. and the drying time is 24 hours.

[0094] The cold pressing pressure is 600Mpa and the time is 30S.

[0095] The sintering process is: firstly heating to 800°C and keeping the temperature for 60 minutes; then heating to 1200°C and keeping the temperature for 3 hours.

[0096] The iron-chromium-aluminum mixed powder is composed of: 70g iron powder, 30g chromium powder, and 6g aluminum powder.

[0097] The plasma spraying process parameters are: 60v, 500A, 30kw.

[0098] The preparation method of the grinding aid is:

[0099] A1: Slowly add 10g of dioctadecylamine (CAS No.: 112-99-2), 0.5g of propylene triphenyltin (CAS No.: 76-63-1), 15g of sodium methacryloyl alginate, and 6g of triethanolamine into 200g of DMF at 90°C, and mix and stir for 60 minutes to ensure that all ingredients are fully dissolved and evenly distributed;

[0100] A2: After mixing and dissolving, DMF is removed by vacuum distillation to obtain a grinding aid.

[0101] The temperature of the reduced pressure distillation is 120° C., the vacuum degree is 100 Torr, and the time is 90 minutes.

[0102] The preparation method of the methacrylated sodium alginate is as follows:

[0103] H1: Dissolve 100 g of sodium alginate in deionized water to form a 5% w / v solution, and adjust the pH to 9 with sodium hydroxide solution;

[0104] H2: At 5°C, slowly drop 80g of methacrylic anhydride and 4g of photoinitiator 2959 into the solution of S1, control the dropping speed to keep the reaction temperature stable, and after the addition is completed, continue to react at 5°C for 5 hours, then continue to stir vigorously at room temperature for 12 hours, place the reaction solution in a dialysis bag and dialyze it in deionized water for 7 days, during which the water is changed 3 times a day, centrifuge the dialyzed solution to collect the supernatant, pre-freeze the supernatant and freeze-dry it in a freeze dryer to obtain methacrylated sodium alginate.

[0105] Comparative Example 1

[0106] No grinding aid was added, and the other procedures were the same as in Example 1.

[0107] Comparative Example 2

[0108] No sodium alginate was added, and the rest was the same as in Example 1.

[0109] Comparative Example 3

[0110] The other steps were the same as in Example 1 except that methacrylic anhydride was not added.

[0111] Table 1

[0112]

[0113] Through the data analysis of the above embodiments and comparative examples, the high-speed railway brake pad prepared by the present invention has a stable friction coefficient, low wear and good wear resistance.

[0114] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-speed rail brake pad, the operating steps of which are: S1: Weigh 110-120 parts of iron powder, 10-15 parts of silicon dioxide powder, 15-20 parts of carbon powder, 20-25 parts of nickel powder, 2-6 parts of copper powder, and 0.007-0.01 parts of grinding aid in parts by weight, put them into a spherical ink tank, put in steel balls, add alcohol, wet grind, dry, and sieve; S2: cold pressing and sintering the sieved powder to obtain a matrix; S3: polishing and removing the substrate, ultrasonic cleaning, heating the iron-chromium-aluminum mixed powder to a molten state, and plasma spraying the surface of the substrate to obtain a high-speed rail brake pad; The grinding aid is prepared by reacting dioctadecylamine, propylene triphenyltin and methacrylic sodium alginate; The preparation method of the grinding aid is: A1: Slowly add 5-10 parts of dioctadecylamine, 0.04-0.5 parts of propylene triphenyltin, 12-15 parts of methacrylated sodium alginate, and 2-6 parts of triethanolamine to 100-200 parts of DMF at 70-90°C, and mix and stir for 30-60 minutes to ensure that all ingredients are fully dissolved and evenly distributed; A2: After mixing and dissolving, DMF is removed by vacuum distillation to obtain a grinding aid.

2. The method for preparing a high-speed railway brake pad according to claim 1, characterized in that: The wet grinding time is 200-270 minutes.

3. The method for preparing a high-speed railway brake pad according to claim 1, characterized in that: The drying temperature is 80-90°C and the drying time is 20-24h.

4. The method for preparing a high-speed railway brake pad according to claim 1, characterized in that: The cold pressing pressure is 400-600Mpa, and the time is 15-30S.

5. The method for preparing a high-speed railway brake pad according to claim 1, characterized in that: The sintering process is: firstly heating to 800°C and keeping the temperature for 40-60min; then heating to 1000-1200°C and keeping the temperature for 1-3h.

6. The method for preparing a high-speed railway brake pad according to claim 1, characterized in that: The iron-chromium-aluminum mixed powder is composed of 60-70 parts of iron powder, 25-30 parts of chromium powder and 2-6 parts of aluminum powder.

7. The method for preparing a high-speed railway brake pad according to claim 1, characterized in that: The plasma spraying process parameters are: 50-60v, 400-500A, 25-30kw.

8. The method for preparing a high-speed railway brake pad according to claim 1, characterized in that: The temperature of the reduced pressure distillation is 80-120° C., the vacuum degree is 50-100 Torr, and the time is 60-90 min.

9. The method for preparing a high-speed railway brake pad according to claim 1, characterized in that: The preparation method of the methacrylated sodium alginate is as follows: H1: Dissolve 80-100 parts of sodium alginate in deionized water to form a solution with a concentration of 1-5% w / v, and adjust the pH value to 8-9 with sodium hydroxide solution; H2: At a temperature of 0-5°C, slowly drop 70-80 parts of methacrylic anhydride and 1-4 parts of photoinitiator 2959 into the solution of S1, control the dropping speed to keep the reaction temperature stable, and after the dropwise addition is completed, continue to react at 0-5°C for 3-5 hours, then continue to stir vigorously at room temperature for 8-12 hours, place the reaction solution in a dialysis bag and dialyze it in deionized water for 7 days, during which the water is changed 2-3 times a day, centrifuge the dialyzed solution to collect the supernatant, pre-freeze the supernatant and freeze-dry it in a freeze dryer to obtain methacrylylated sodium alginate.

Citation Information

Patent Citations

  • Powder metallurgy brake pad and preparing method thereof

    CN109185369A

  • A method for preparing a high thermal conductivity copper-based brake pad with an oriented structure

    CN110715005B

  • A method for preparing copper-based brake pad material, its product and application

    CN115233019B

  • Liquid grinding aid

    CN101643338A

  • Copper-based powder metallurgy brake pad material as well as preparation method and application thereof

    CN108118181A